Study and Designing of Digital Three-Dimension Space Visualizer for Centralize Drone Performance - Kiun, Sie Suai [ (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Method and algorithm to generate flexible paths of UAVs has been very crucial research area since recent years. This study’s goal is to able generating flexible paths for UAVs. This paper will present practical algorithm for generating the paths for drone in any workspace with obstacle and neglect other constraint. A framework will be created base on the algorithm make using Delaunay Triangulation method which discussed in chapter 3. This paper presents a new paths method for motion planning which using Delaunay Triangulation in order to form platonic shape of path in 3D free configuration space. The main novelty of our approach is that the candidate points are chosen on configuration space free from obstacle. This approach to use for collision free point and generating the path using Delaunay Triangulation. The manipulation of the shape can be done by adding it the point to generate more tetrahedrons. The generated paths of UAVs are successful if the path is collision-free and able flexibly change the workspace size.